The extent of edema and tumor synchronous invasion into the subventricular zone and corpus callosum classify outcomes and radiotherapy strategies of glioblastomas. Issue 2 (November 2017) - Liang, Hsiang-Kuang Tony; Chen, Wan-Yu; Lai, Shih-Fan; Su, Mao-Yuan; You, San-Lin; Chen, Liang-Hsin; Tseng, Ham-Min; Chen, Chung-Ming; Kuo, Sung-Hsin; Tseng, Wen-Yih Isaac
Abstract: Background and purpose: Irradiating glioblastoma preoperative edema (PE) remains controversial. We investigated the associations between tumors' PE extent with invasion into synchronous subventricular zone and corpus callosum (sSVZCC) and treatment outcomes to provide the clinical evidence for radiotherapy decision-making. Material and methods: Extensive PE (EPE) was defined as PE extending ≥2 cm from the tumor edge and extensive progressive disease (EPD) as tumors spreading ≥2 cm from the preoperative tumor edge along PE. The survival and progression patterns were analyzed according to EPE and sSVZCC invasion. Results: In total, 136 patients were followed for a median of 74.9 (range, 47.6–102.1) months. The median overall survival and progression-free survival were 19.7 versus 28.6 months ( p  = 0.005) and 11.0 versus 17.4 months ( p  = 0.011) in patients with EPE+ versus EPE−, and were 18.7 versus 25.4 months ( p  = 0.021) and 10.7 versus 14.6 months ( p  = 0.020) in those with sSVZCC+ versus sSVZCC−. The EPD rates for tumors with EPE−/sSVZCC−, EPE−/sSVZCC+, EPE+/sSVZCC−, and EPE+/sSVZCC+ were 2.8%, 7.1%, 37.0%, and 71.9%, respectively. In EPE+/sSVZCC+, tumor migration was associated with the PE extending along the corpus callosum (77.8%) and subventricular zone (50.0%). Conclusions: Our results support the need for developing individualized irradiation strategies for glioblastomas according to EPE and sSVZCC.